Kartun Islami sebagai Media Pembelajaran Bahasa Indonesia untuk Meningkatkan Akhlak Mulia Peserta Didik - Eliana Eliana (Ameena Journal, 2025)
Indonesian language learning not only develops students’ listening, speaking, reading, and writing skills but can also serve as a means of cultivating their moral character. However, the use of Islamic cartoons as a medium that integrates language learning with moral education has not been extensively examined. This study aims to analyze the potential and use of Islamic cartoons as an Indonesian language learning medium for strengthening students’ noble character. The study employed a library research method by collecting and examining relevant written sources, including books, scholarly articles, previous research, and educational documents. The data were analyzed descriptively and interpretatively through classification, comparison, and interpretation based on the focus of the study. The findings indicate that Islamic cartoons can support the development of listening, speaking, reading, and writing skills through visual images, dialogues, storylines, and characters’ behavior. This medium can also introduce and reinforce the values of honesty, responsibility, politeness, discipline, social concern, and respect for others. Islamic cartoons make the learning process more engaging, contextual, and accessible to students. Their effectiveness depends on the suitability of the content for learning objectives and the teacher’s ability to guide students in understanding linguistic messages and moral values. This study concludes that Islamic cartoons can function as an integrative medium in Indonesian language learning. It contributes to the development of language-learning media that simultaneously improve language proficiency and strengthen students’ noble character.